2016
DOI: 10.1039/c5lc01515d
|View full text |Cite
|
Sign up to set email alerts
|

A microfluidic method for dopamine uptake measurements in dopaminergic neurons

Abstract: Dopamine (DA) is a classical neurotransmitter and dysfunction in its synaptic handling underlies many neurological disorders, including addiction, depression, and neurodegeneration. A key to understanding DA dysfunction is the accurate measurement of dopamine uptake by dopaminergic neurons. Current methods that allow for the analysis of dopamine uptake rely on standard multiwell-plate based ELISA, or on carbon-fibre microelectrodes used in in vivo recording techniques. The former suffers from challenges associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 46 publications
(94 reference statements)
1
24
0
Order By: Relevance
“…Numerous microchannel-based microfluidic platforms have been used to evaluate neurotransmitter release from neuronal cells 20,21 , but these platforms have not been applied to this problem; moreover, we are unaware of any system that is capable of evaluating both neurotransmitter uptake and release. The closest system was our previous method 19 , which had separate modules for (a) cell culture and (b) DA electroanalysis. Here, we sought to combine (a) and (b) into a single, integrated unit known as a “cell-culture/electroanalytical sensor” (or “c-e-sensor”) that allows for the continuous monitoring of DA homeostasis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous microchannel-based microfluidic platforms have been used to evaluate neurotransmitter release from neuronal cells 20,21 , but these platforms have not been applied to this problem; moreover, we are unaware of any system that is capable of evaluating both neurotransmitter uptake and release. The closest system was our previous method 19 , which had separate modules for (a) cell culture and (b) DA electroanalysis. Here, we sought to combine (a) and (b) into a single, integrated unit known as a “cell-culture/electroanalytical sensor” (or “c-e-sensor”) that allows for the continuous monitoring of DA homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“…In response to the challenge described above, we developed an automated digital microfluidic (DMF) platform that integrates in vitro cell culture 15,16 with electrochemical analysis 17,18 . We recently described an initial solution to this problem 19 , i.e., a microfluidic device that includes (1) a cell-culture module designed for multi-day dopaminergic neuron culture and (2) a quantitative amperometric DA sensor (“e-sensor”) module. A key limitation to this previous method 19 is its modular nature, i.e., droplets of culture medium are shuttled between the two modules, rendering continuous measurements impossible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first time EIS was used to monitor the media exchange during passive dispensing in a virtual microwell. Passive dispensing is a well-known mechanism in DMF to allow precise fluid incubation underneath a hydrophilic spot in the top chip [ 14 , 53 , 55 , 57 , 71 , 72 ]. Barbulovic-Nad et al showed by fluorescence measurements that three source droplets are necessary to fully exchange the volume of the virtual microwell completely [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…They integrate an Ag/AgCl on-chip pseudo-reference electrode into the DMF device and use voltammetry achieving a sensor response close to Nernstian behavior. Yu et al monitor the dopamine uptake in neurons by cyclic voltammetry (CV) integrated in DMF [ 53 , 54 ]. Dryden et al use integrated electrodes for linear sweep voltammetry (LSV) measurements of different acetaminophen concentrations generated by repeated dilution using the EWOD fluid handling capabilities bearing a limit of detection of 76 μM [ 55 ].…”
Section: Introductionmentioning
confidence: 99%